Biochar Affects Essential Nutrients of Carrot Taproots and Lettuce Leaves - Olszyk, David M (HortScience : a publication of the American Society for Horticultural Science, 2020)
Essential nutrient concentrations in crops can affect human health. While biochar has the potential as a soil amendment to improve crop yields, it may also affect the concentrations of nutrients such as Ca, Fe, K, Mg, Mn, and Zn in edible portions of crops. To better characterize effects of biochar on important human nutrients in food crops, we evaluated the effects of biochar on lettuce (Lactuca sativa L. cv. Black-Seeded Simpson) leaf and carrot [Daucus carota subsp. sativus (Hoffm.) Schübl. cv. Tendersweet] developing taproot nutrients. Plants were grown in pots in a greenhouse using sandy loam (Coxville, fine, kaolinitic, thermic Typic Paleaquults) and loamy sand (Norfolk, fine-loamy, kaolinitic, thermic Typic Kandiudults,) series soils, amended with biochar produced from four feedstocks: pine chips (PC), poultry litter (PL), swine solids (SS), and switchgrass (SG); and two blends of PC plus PL [Pc/PL, 50%/50% (55) and 80%/20% (82) by weight]. Biochar was produced at 350, 500, and 700 °C from each feedstock. Lettuce leaf and carrot taproot total nutrient concentrations were determined by inductively coupled plasma analysis. Biochar (especially at least in part manure-based, i.e., PL, SS, 55, and 82 at nearly all temperatures) primarily decreased nutrient concentrations in lettuce leaves, with Ca, Mg, and Zn affected most. Carrot taproot nutrient concentrations also deceased, but to a lesser extent. Some biochars increased leaf or taproot nutrient concentrations, especially K. This study indicated that biochar can both decrease and increase leaf and taproot nutrient concentrations important for human health. Thus, potential effects on nutrients in plants should be carefully considered when biochar is used as a soil amendment with vegetable crops